ANALISIS MINAT BELAJAR SISWA MELALUI MEDIA MONOPOLI KERAGAMAN SUKU (MORASU) PADA TEMA 7 SUB TEMA 1 KELAS IVB DI SDN 2 SURODAKAN KABUPATEN TRENGGALEK - Krisca Renanda Aprilistiandita Krisca (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Interest in learning for IVB graders at Surodakan Elementary School 2, Trenggalek Regency is less than optimal. This condition is characterized by the presence of students who are less active and busy themselves. So that researchers conduct research to find out how much students interest in following the learning process. To find out the interest in learning students, learning media is used. One of the media used is the media monopoly on ethnic diversity (morasu). The media is adapted to the learning material in class IVB students. This study uses descriptive qualitative methods. All problems and results will be explained in detail according to the conditions in the field. The research subjects were IVB graders, which numbered 34 students. To obtain information, researchers as the main instrument will be assisted with supporting instruments, namely observation instruments, interviews, questionnaires and documentation. Based on the analysis of the data obtained, class IVB students showed greater interest in learning when learning using monopoly media. It can also be a lesson for teachers to be more creative. High interest in learning will give good results for further learning.